Expectations concerning cancer treatment: perspectives of medical oncologists and patients on advanced, unresectable lung carcinoma - Cruz-Castellanos, Patricia; Jiménez-Fonseca, Paula; Galán-Moral, Rocío; Piera-Molons, Nuria; Gustems, Marina; Calderon, Caterina (Frontiers in Psychology, 2024)
Introduction This study seeks to compare expectations regarding systemic cancer treatment for advanced lung cancer from the perspectives of both patient and medical oncologist. Methods A cross-sectional study involving 17 medical oncologists from 13 Spanish hospitals between 2021 and 2022. Patients with advanced, unresectable lung cancer were recruited prior to initiating systemic cancer treatment. Both patients and oncologists completed the NEOetic-EIT and the STAR. Results Seventeen medical oncologists specializing in lung cancer participated, with a mean age of 36.2 years (range 28–56); 65% were female. The study included 298 patients with advanced, unresectable lung cancer, predominantly non-small cell type (72%), and most at stage IV (77%). Most patients were retired or unemployed (71%), and married or partnered (77%). Treatment approaches varied, with 44% based on biomarkers. Oncologists had greater expectations of positive outcomes for participants with better baseline prognosis, such as ECOG 0, newly diagnosed, locally advanced, unresectable non-small cell lung cancer, and those receiving biomarker-based treatments. In contrast, patients’ treatment expectations did not vary based on sociodemographic or clinical factors. Generally, patients had high expectations of cure, in contrast to oncologists’ lower expectations, though both anticipated similar quality-of-life improvements. Patients anticipated more side effects than oncologists. Among oncologists, expectations varied by gender and decreased with age and experience, with no differences detected among patients based on gender, age, or doctor-patient relationship. Conclusion This study reveals the complex expectations of patients and oncologists in advanced lung cancer treatment. It underscores the need for effective communication in oncology to align patient expectations with clinical realities.